PENGARUH PENERAPAN MODEL DISCOVERY LEARNING TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS VII PADA MATERI SUMBER ENERGI DI SMP NEGERI 1 KUPANG TAHUN AJARAN 2018/2019 - Zoulon Yohanes Ivaldus (Program Studi Pendidikan Biologi Universitas Katolik Widya Mandira, 2023)
One of the reasons for the low learning outcomes of students is that the learning process in the classroom is still centered on the teacher. The learning model that is able to increase the activeness of students in the classroom is the discovery learning model. The purpose of this study was to determine the effect of the discovery learning model on the learning outcomes of class XI science students on the Coordination System material at SMA Negeri 5 Kupang.The type of research used is quantitative research with Quasi Experiment method. The design used in this study is the Noneequivalent control group design. The results showed that the average student learning outcomes in the experimental class obtained a pretest score of 41.86 which increased to 80.31 after being given a posttest. Meanwhile, in the control class, the pretest score was 45.47 which increased to 74.11 after being given a posttest. Based on the results of the one-way Anacova test, the probability value (sig) of 0.000 is smaller than the set value of 0.05. This shows that Ha (discovery learning model has an effect on student learning outcomes) is accepted and H0 (discovery learning model has no effect on student learning outcomes) is rejected. Based on the results of data analysis, it can be concluded that the discovery learning model has an effect on the learning outcomes of class XI students on the coordination system material at SMA Negeri 5 Kupang.